Privacy-Preserving Techniques in Smart Metering: An Overview - Barbosa, Pedro; Freitas, Lucas; Brito, Andrey; Silva, Leandro (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2016)
Smart energy meters grant to power providers the capability to perform many advanced services, and several countries already started to deploy them. However, data analysis can raise privacy issues by inferring daily activities and appliance usages of consumers. Hence, there is a crucial need to deal with the problem of consumers' privacy in smart metering. Several approaches offer ways to provide privacy and preserve some of the benefits. In this paper, we list, experiment and evaluate five of these approaches based on three orthogonal technologies: noise addition, rechargeable batteries, and homomorphic encryption. We evaluate them based on the main needed attributes, such as complexity and accuracy, and conclude that there are many tradeoffs to be dealt with.